Reconstructive surgery for male stress urinary incontinence: Experiences using the ATOMS system at a single center - Krause, Jens; Tietze, Stefan; Behrendt, Wolf; Nast, Jenifer; Hamza, Amir (GMS Interdisciplinary Plastic and Reconstructive Surgery DGPW, 2014)
Objective: To propose possible success-driven solutions for problem and complication rates encountered with the ATOMS sling system, based on first-hand experience; and to provide possible actual alternative scenarios for the treatment of male . Patients and methods: During the defined period (between 4/2010 and 04/2014), 36 patients received ATOMS system implants at our clinic. We collected pre- and post-operative evaluation data using the International Consultation on Incontinence Questionnaire Short Form (ICIQ SF). As an expansion of the questionnaire, we added questions about post-operative perineal pain, the general satisfaction with the results of the intervention and willingness to recommend the operation to a best friend. Results: Our data shows a relatively high explantation rate, but a surprisingly high patient satisfaction rate. Explantation was required mainly due to late onset infections or other symptomatic factors. Compared to other studies early onset infections were rare. Conclusion: A non-invasive, uncomplicated adjustable system to alleviate male stress urinary incontinence remains a challenge. Although there are various systems available for the treatment of male stress urinary incontinence, it seems that despite the advantages of the ATOMS system, an artificial sphincter system may pose more advantages based on our experience, understanding and knowledge of its well-documented long-term solutions and problems.